A Reassessment of Augustine’s Theological Thought and Its Contemporary Relevance - Mawikere, Marde Christian Stenly; Hura, Sudiria (PT. Giat Konseling Nusantara, 2024)
The theological thought of Augustine remains relevant in addressing the challenges of the modern era, including secularism, moral relativism, and the crisis of Church authority. This study examines the concepts of original sin, grace, predestination, and the relationship between faith and reason within a contemporary context. Through a content analysis of scholarly literature, it is observed that Augustine’s ideas provide ethical and spiritual guidance for both the Church and society. Furthermore, the concept of Civitas Dei offers a perspective on the Church’s role amidst social transformations. Augustine’s theological legacy serves as a profound reflection for Christians navigating the complexities of the modern world.